Job Opportunity, Attitudes, Perceived Behavioral Control and Intention to Major in Accounting - Gainau, Paskanova Christi (AKRUAL: JURNAL AKUNTANSI, 2021)
This research aims to capture the accounting behavior phenomenon in accounting students at private universities in Manado. This research is developed from the study of Lin & Fawzi (2006), Zandi et al.(2013), and Odia & Ogiedu (2013). To find out the inconsistency of these researches, this research focus to study about the students’s intention in choosing an accounting program. Partial least square is used to analyze the research model. This study used questionnaires and deep interviewed to collect the data. It reveals that job opportunities deliver positive effects on accounting students’s attitudes, and these attitudes affect their intention to select the program. The reputation on higher education institutions on accounting do not determine the students’s attitudes to enroll in accounting. Subjective norm do not influence students intention. Perceived behavior control positively encourages   the purposeof choosing the accounting program. These findings designate implications for accounting lecturers to explain the benefits, job opportunities, and temporary accounting issues to students. Management of the accounting department needs to re-design their curriculum; thus, it can drive college students to compete and have fun throughout the learning process. Lecturers are obligated to update their learning methods and include educational characters in the provision of material to increase students's motivation.